The phenomenon of thought in the theory of knowledge M.K. Mamardashvily (Journal of Philosophy Culture and Political Science, 2018)
Mamardashvily actualized metaphisical base and transcendental spheres of thinking, focus on world view importance of thinking as thought. Thought of citizen and philosopher, able to create specific thinking space of uncertainty. The methodological, understanding, and common cultural role of phenomenon of thought, intellectual intuition, freedom, responsibility, religious experience in formation of philosophical views of M.K Mamardashvily was fixed. M.K. Mamardashvily actualized the historical-philosophical heritage of Parmenides, Plato, Aristotles, Avgustine, B. Pascal, R. Descartes, I. Kant, M. Prust rethinking and reviving the question of thinking that is fundamental for the history of philosophy, within its religious tradition, metaphysical base, transcendental sphere, and worldview importance of thinking as thought. M.K. Mamardashvily applied his acquired knowledge and philosophical establishment based on them for the benefit of society, believes that its his citizen’s duty to teach the people the culture of philosophical thinking, at the same time not to impose on anybody his theoretical and philosophical ideas. The historical-logical consequence of philosophy of Mamardashvily is his original dialogue with philosophical heritage of R. Descartes, I. Kant, M. Prust and this dialogue was realized as cultural-historical event within the best tradition of germeneftics and phenomenological philosophy and bears in itself the great influence in understanding and estimating the such historical philosophers as G.W.F. Hegel, F.W. Schelling, V. Dyltey, K. Jaspers, K. Fisher, N. Berdyiaev, B. Rassel on the history of philosophy. Key words: of M.K. Mamardashvily, the theory of knowledge, idea, thought, consciousness, phenomenology, phenomenon.